2018
DOI: 10.1021/acs.biochem.7b01102
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Studies of Asp632 Mutants and Fully Reduced NADPH-Cytochrome P450 Oxidoreductase Define the Role of Asp632 Loop Dynamics in the Control of NADPH Binding and Hydride Transfer

Abstract: Conformational changes of NADPH-cytochrome P450 oxidoreductase (CYPOR) associated with electron transfer from NADPH to electron acceptors via FAD and FMN have been investigated through structural studies of the 4-electron-reduced NADP+-bound enzyme and kinetic and structural studies of mutants affecting the conformation of the mobile Gly631-Asn635 loop (Asp632 loop). The structure of 4-electron-reduced, NADP+-bound wild type CYPOR shows the plane of the nicotinamide ring positioned perpendicular to the FAD iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 56 publications
(172 reference statements)
2
21
0
Order By: Relevance
“…Then, the redox state change, which is accompanied by the net charge change, could affect the electrostatic interaction between the FAD and the FMN domains. Binding of NADP + , which carries net negative charge, could also affect the interaction between the two domains, triggered by local rearrangement of the electrostatic bonds; Actually, such rearrangement of the electrostatic bonds involving Asp632, which is located near the binding site of NADP + and was noticed in the recent structural studies 27,28 , was observed in our MD simulation (data not shown). In addition, the redox state change in FMN (and also in heme) should affect the electrostatic interaction between the FMN domain and monooxygenase 29 .…”
Section: Discussionsupporting
confidence: 48%
“…Then, the redox state change, which is accompanied by the net charge change, could affect the electrostatic interaction between the FAD and the FMN domains. Binding of NADP + , which carries net negative charge, could also affect the interaction between the two domains, triggered by local rearrangement of the electrostatic bonds; Actually, such rearrangement of the electrostatic bonds involving Asp632, which is located near the binding site of NADP + and was noticed in the recent structural studies 27,28 , was observed in our MD simulation (data not shown). In addition, the redox state change in FMN (and also in heme) should affect the electrostatic interaction between the FMN domain and monooxygenase 29 .…”
Section: Discussionsupporting
confidence: 48%
“…As anticipated, in addition to con-served residues of Cys347 and Thr241, both Arg233 and Asp74 could remarkably affect the activity of HmtS-L340F from the mutagenesis. In the complexed model consisting of enzyme, NADPH and riboflavin, Arg233 is the site to bind riboflavin ( Figure S17 and S18), and Asp74, similar to the situation of Asp632 in NADPH-cytochrome P450 oxidoreductase, 29 is responsible for the binding with NADPH ( Figure S20). Not surprisingly, the significant reduction of activity from the mutations of Arg233 and Asp74 was in accordance with the results of MD simulation.…”
Section: Biochemical Analyses Confirmed the Electron Transfer Processmentioning
confidence: 85%
“…The areas of greatest deshielding are seen in (i) the hinge domain of the CPR, (ii) within the beta-sheets of the CPR FMN domain, and (iii) in a peripheral alpha helix within the FMN domain (L2). Studies have suggested that NADP + binding to the CPR domain induces a closed conformation in which the FAD and FMN cofactors are a short distance apart (ca 4 Å) (38). On reduction by NADPH, an open conformation is adopted as the FAD/NADPH-and FMNbinding domains move apart to enable FMN domain/heme domain interactions (38).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that NADP + binding to the CPR domain induces a closed conformation in which the FAD and FMN cofactors are a short distance apart (ca 4 Å) (38). On reduction by NADPH, an open conformation is adopted as the FAD/NADPH-and FMNbinding domains move apart to enable FMN domain/heme domain interactions (38). An important residue for the dissociation of NADP + is Ser634.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation